An Arabidopsis soluble chloroplast proteomic analysis reveals the participation of the Executer pathway in response to increased light conditions. (4th March 2015) - Uberegui, Estefanía; Hall, Michael; Lorenzo, Óscar; Schröder, Wolfgang P.; Balsera, Mónica
Highlight: Executer proteins have emerged as participants in singlet oxygen-mediated retrograde signalling in plants. This study relates the function of Executer in chloroplasts with the acclimation response to increased light. Abstract: The Executer1 and Executer2 proteins have a fundamental role in the signalling pathway mediated by singlet oxygen in chloroplast; nonetheless, not much is known yet about their specific activity and features. Herein, we have followed a differential-expression proteomics approach to analyse the impact of Executer on the soluble chloroplast protein abundance in Arabidopsis . Because singlet oxygen plays a significant role in signalling the oxidative response of plants to light, our analysis also included the soluble chloroplast proteome of plants exposed to a moderate light intensity in the time frame of hours. A number of light- and genotype-responsive proteins were detected, and mass-spectrometry identification showed changes in abundance of several photosynthesis- and carbon metabolism-related proteins as well as proteins involved in plastid mRNA processing. Our results support the participation of the Executer proteins in signalling and control of chloroplast metabolism, and in the regulation of plant response to environmental changes.